MicroRNAs contribute to ATP-binding cassette transporter- and autophagy-mediated chemoresistance in hepatocellular carcino - Espelt, Maria Victoria (2019)
Hepatocellular carcinoma (HCC) has an elevated mortality rate, largely because of high recurrence and metastasis. Additionally, the main obstacle during treatment of HCC is that patients usually develop resistance to chemotherapy. Cancer drug resistance involves many different mechanisms, including alterations in drug metabolism and processing, impairment of the apoptotic machine, activation of cell survival signaling, decreased drug sensitivity and autophagy, among others. Nowadays, miRNAs are emerging as master regulators of normal physiology- and tumor-related gene expression. In HCC, aberrant expression of many miRNAs leads to chemoresistance. Herein, we particularly analyzed miRNA impact on HCC resistance to drug therapy. Certain miRNAs target ABC (ATP-binding cassette) transporter genes. As most of these miRNAs are downregulated in HCC, transporter levels increase and intracellular drug accumulation decrease, turning cells less sensitive to death. Others miRNAs target autophagy-related gene expression, inhibiting autophagy and acting as tumor suppressors. Nevertheless, due to its downregulation in HCC, these miRNAs do not inhibit autophagy or tumor growth and, resistance is favored. Concluding, modulation of ABC transporter and/or autophagy-related gene expression or function by miRNAs could be determinant for HCC cell survival under chemotherapeutic drug treatment. Undoubtedly, more insights on the biological processes, signaling pathways and/or molecular mechanisms regulated by miRNAs are needed. Anyway, miRNA-based therapy together with conventional chemotherapeutic drugs has a great future in cancer therapy.